The Impact of the COVID-19 Pandemic on Research into Chinese University Students’ Mental Health: A Bibliometric Analysis - Zhexian Zhu; Michela Montesi (Journal of Library and Information Studies)
Background: The COVID-19 pandemic increased anxiety and depression rates, prompting heightened research activity in mental health, particularly among vulnerable populations like university students. Research activity adapted in order to address issues arising in this new landscape. Objectives: This study aims to explore the changes in scientific activity and response trends during a public health crisis, with a particular focus on analyzing research themes, categories, and collaboration patterns related to the mental health of Chinese university students before and after the COVID-19 pandemic. Method: Using bibliometric methods, data were extracted from Web of Science to analyze scientific output related to the mental health of Chinese university students from 2017 to 2022. Descriptive statistics and visual analysis tools were employed to explore publication trends and collaboration patterns. Discussion: After the pandemic, there is an increase in the total amount of literature and open-access publications. Research topics have shifted towards prioritizing student well-being over clinical diagnoses. Strengthened international and institutional collaboration is evident through increased cooperation with developing countries and those heavily impacted by the pandemic, as well as intensified partnerships between medical universities and prestigious academic institutions. Conclusions: The findings of this research can guide supportive efforts by libraries, academic journals, international partnerships, and funding bodies to address mental health challenges during future epidemics. Furthermore, they highlight the value of collaboration between bibliometrics and psychology in tackling the complex issues surrounding mental health in such contexts. Professionals in bibliometrics and psychology should collaborate to address the complex challenges posed by mental health and future epidemics.